Thyroidectomy in a Surgical Volunteerism Mission: Analysis of 464 Consecutive Cases. (28th November 2019) - Latifi, Rifat; Gachabayov, Mahir; Gogna, Shekhar; Rivera, Renato
Abstract : Although surgical volunteer missions (SVMs) have become a popular approach for reducing the burden of surgical disease worldwide, the outcomes of specific procedures in the context of a mission are underreported. The aim of this study was to evaluate outcomes and efficiency of thyroid surgery within a surgical mission. This was a retrospective analysis of medical records of all patients who underwent thyroid surgery within a SVM from 2006 to 2019. Postoperative complication rate was the safety endpoint, whereas length of hospital stay (LOS) was the efficiency endpoint. Serious complications were defined as Clavien–Dindo class 3–5 complications. Expected safety and efficiency outcomes were calculated using the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) surgical risk calculator and compared to their observed counterparts. A total of 464 thyroidectomies were performed during the study period. Mean age of the patients was 40.3 ± 10.8 years, and male-to-female ratio was 72 : 392. Expected overall (p = 0.127 ) and serious complication rates (p = 0.738 ) were not significantly different from their observed counterparts. Expected LOS was found to be significantly shorter as compared to its observed counterpart (0.6 ± 0.2 vs. 2.5 ± 1.0 days; p < 0.001 ). This study found thyroid surgery performed within a surgical mission to be safe. NSQIP surgical risk calculator underestimates the LOS following thyroidectomy in surgical missions.